ORPORATE SOCIAL RESPONSIBILITY: IMPLIKASI STAKEHOLDER DAN LEGITIMACY GAP DALAM PENINGKATAN KINERJA PERUSAHAAN - Marsella Puspita (Ma Chung Press, 2015)
This study purpose explaination some of the significance theories inorder to establishing the CSR concept for the company. This responsibility is communicated by the company to its stakeholders through the disclosure of Corporate Social Responsibility (CSR). CSR is provided by the management to stakeholders, potential investors about the future company's prospects and show the company’s value by the impact on the economic, social and environment from its activities. The differences of interest between company and societies in term of valuation and expectations created the legitimacy gap. In the theoretical concepts explained CSR disclosure by the company can minimize the legitimacy gap.